2017
DOI: 10.1002/jbm.a.36191
|View full text |Cite
|
Sign up to set email alerts
|

The extracts of bredigite bioceramics enhanced the pluripotency of human dental pulp cells

Abstract: Biomaterials have a profound effect on tissue engineering and regenerative medicine, but few studies have reported the role of extracts from bioceramics in the regulation of stem cell pluripotency. The present study investigated the effects of bioceramics extracts, including silicate bredigite (Ca7MgSi4O16) and conventional β‐tricalcium phosphate (β‐TCP), on the pluripotency and the multilineage differentiation potential of human dental pulp cells (hDPCs). Basic fibroblast growth factor (bFGF), which is a know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…10−12 Furthermore, by releasing a variety of ionic products, BRT bioceramics may regulate the biological behavior of stem cells and enhance the ability of cell lineage differentiation. 13,14 Based on the comprehension of osteoimmunology, the complex interaction between biomaterial and host cells is considered a determinant factor for the fate of biomaterial implantation. 15,16 Immediately after the implantation of bone biomaterial, the host immune response is initiated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10−12 Furthermore, by releasing a variety of ionic products, BRT bioceramics may regulate the biological behavior of stem cells and enhance the ability of cell lineage differentiation. 13,14 Based on the comprehension of osteoimmunology, the complex interaction between biomaterial and host cells is considered a determinant factor for the fate of biomaterial implantation. 15,16 Immediately after the implantation of bone biomaterial, the host immune response is initiated.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Meanwhile, as reported by Chen et al, bredigite extracts significantly promoted human dental pulp cells (hDPCs) growth, proliferation, and multilineage differentiation, whereas β-TCP extracts lacked these properties. 13 On the one hand, the osteoimmunomodulation of biomaterials originates from the release of bioactive ions. Ca and Mg are two essential elements in the natural bone tissues affecting bone regeneration directly.…”
mentioning
confidence: 99%
“…Previously Hench et al showed that approximately 17-21 ppm of soluble Si and 60-88 ppm of soluble Ca ions were required for osteoblasts to grow, differentiate and form a mineralized extracellular matrix and create bone nodules [40]. In a study by Chen et al [41], it was shown that the exposure of 50 mg/mL bredigite extracts had a profound effect in delaying cell senescence, stimulating pluripotency-related gene expression and enhancing odontogenic and adipogenic differentiation. In the same study, it was reported that the release of Si species in the extract had a great contribution towards the cellular changes observed [41].…”
Section: Figurementioning
confidence: 99%
“…In a study by Chen et al [41], it was shown that the exposure of 50 mg/mL bredigite extracts had a profound effect in delaying cell senescence, stimulating pluripotency-related gene expression and enhancing odontogenic and adipogenic differentiation. In the same study, it was reported that the release of Si species in the extract had a great contribution towards the cellular changes observed [41]. As shown, hDPCs in the BG groups proliferated throughout the culture period showing that the ions liberated from BG at various time intervals did not have an inhibitory effect on cells.…”
Section: Figurementioning
confidence: 99%
“…In the present study, we showed the osteogenic potential of iPSCs for bone regeneration applications through their culturing onto strontium (Sr)- and cobalt (Co)-substituted BGs that previously synthesized and characterized (Kargozar et al, 2016). Although osteogenic differentiation of iPSCs were evaluated in contact with some types of ceramics (e.g., akermanite and bredigite) (Dong et al, 2016; Chen et al, 2017), to the best knowledge of the authors, it is the first report on the applicability of simultaneous use of iPSCs and BGs regarding BTE applications, which can be considered a pioneer work in this important field. With respect to the promising features of both BGs and iPSCs, it could be interesting to evaluate their combination for bone reconstruction.…”
Section: Introductionmentioning
confidence: 99%